PUBLIC POLICY AND INEQUALITY IN NIGERIA: AN INTERROGATION - MOSES DANJUMA BOT; MARIA ELEYI IGOCHE; ANOMNIHE UDOKA TIMDIR (International Studies Journal)
Inequality is a pressing issue in many societies and Nigeria in particular and policymakers face the challenge of creating effective policies to address it. This is why people-based policymaking is germane in developing policies that are tailored to the specific needs of different groups. Hence, addressing the root causes of inequality, it is possible to create a more just and equitable society for all. The paper adopts a qualitative research design, drawing on secondary sources such as policy documents, scholarly articles, official reports, relevant blog post, newspapers and books to examine the correlation and impact of public policy on inequality in Nigeria. Using content analysis, the study identified themes and patterns in the sourced secondary data and equally interpret the findings using the Pareto principle which states that a small number of causes are responsible for the majority of outcomes, can help to identify the most important factors that need to be addressed. The study recommends that the government should prioritize the fight against systematic corruption in Nigeria by allowing the principle of the rule of law prevail. The study also recommends for an increase in funding for social safety net programs, such as unemployment benefit, food assistance, in order to help reduce poverty and inequality.